Atemoya Growing in the Florida Home Landscape - Jonathan H. Crane; Carlos F. Balerdi; Ian Maguire (EDIS, 2006)
Revised! HS-64, a 10-page fact sheet by Jonathan H. Crane, Carlos F. Balerdi, and Ian Maguire, provides homeowners with an expanded and reorganized basic reference for growing atemoya in the home landscape. Tables include information on cultural practices by month, fertilizer program, and flowering behavior. Included in the Master Gardener Handbook. Published by the UF Horticultural Sciences Department, October 2005.